Yes there is a solution for 6-3+4x+1 it is
4+4x because u add up all the like terms or variable
Below are the choices that can be found elsewhere:
<span>a. $1,158.33
b. $1,069.23
c. $2,316.66
d. $1,539.22
</span>
Below is the solution:
$27,800 / 12 months = 2,316
$2,316 / 2 since it bi-monthly = $1,158.33
Thank you for posting your question here. I hope the answer helps.
Answer:
<h2>The easiest to solve for is x in the first equation</h2>
Step-by-step explanation:
Given the system of equation, x + 4 y = 14. and 3 x + 2 y = 12, to solve for x, we can use the elimination method of solving simultaneous equation. We need to get y first.
x + 4 y = 14............ 1 * 3
3 x + 2 y = 12 ............ 2 * 1
Lets eliminate x first. Multiply equation 1 by 3 and subtract from equation 2.
3x + 12 y = 42.
3 x + 2 y = 12
Taking the diffrence;
12-2y =42 - 12
10y = 30
y = 3
From equation 1, x = 14-4y
x = 14-4(3)
x = 14-12
x = 2
It can be seen that the easiest way to get the value of x is by using the first equation and we are able to do the substitute easily <u>because the variable x has no coefficient in equation 1 compare to equation 2 </u>as such it will be easier to make the substitute for x in the first equation.
U need to simplify 5×5 to 25,move the negative to the left, then simplify the brackets
Answer:
7/6
Step-by-step explanation:
7/3÷4/5
7/3×5/4
35/12
Now the multiplication
2/5×35/12
70/60
7/6